1988
DOI: 10.1159/000124958
|View full text |Cite
|
Sign up to set email alerts
|

Regional Specificity of Gamma-Aminobutyric Acid Receptor Regulation by Estradiol

Abstract: In vitro quantitative autoradiography and the microdissection technique of Palkovitz were used to examine the effects of estradiol-17β on GABAAreceptors and on glutamic acid decarboxylase in discrete areas of rat brain. Under the conditions examined, estradiol did not affect glutamic acid decarboxylase activity. However, treatment with estradiol decreased Gabaa receptor binding in a majority of areas that contain high levels of intracellular estradiol receptors and in a number of areas that contain few or no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 22 publications
(28 reference statements)
4
41
0
Order By: Relevance
“…Differences within the hypothalamus/basal forebrain as a function of sex or hormonal state in the expression of other GABA A receptor subunits (Clark et al, 1998;Nett et al, 1999;Penatti et al, 2005), in the numbers of GABA A receptors and in their binding affinities (O'Connor et al, 1988;Lasaga et al 1988;Schumacher et al, 1989;Juptner and Hiemke, 1990) have also been reported. It is likely that these differences play significant roles with respect to the expression of sexual and reproductive behaviors, but their impact on allosteric modulation of GABA A receptors in these brain regions or the potential outcome of such modulation on the expression of sexual or reproductive behaviors is currently not known.…”
Section: Steroid Modulation Of Gabaergic Transmission In Hypothalamusmentioning
confidence: 99%
“…Differences within the hypothalamus/basal forebrain as a function of sex or hormonal state in the expression of other GABA A receptor subunits (Clark et al, 1998;Nett et al, 1999;Penatti et al, 2005), in the numbers of GABA A receptors and in their binding affinities (O'Connor et al, 1988;Lasaga et al 1988;Schumacher et al, 1989;Juptner and Hiemke, 1990) have also been reported. It is likely that these differences play significant roles with respect to the expression of sexual and reproductive behaviors, but their impact on allosteric modulation of GABA A receptors in these brain regions or the potential outcome of such modulation on the expression of sexual or reproductive behaviors is currently not known.…”
Section: Steroid Modulation Of Gabaergic Transmission In Hypothalamusmentioning
confidence: 99%
“…Steroids reduce GAD concentration in the ventral tegmentum, septum and substantia nigra (6,34,35) and daily injections of OB, that would inhibit LH release and stimulate prolactin release, induce changes in GAD activity in a number of hypothalamic regions; some reports have shown that mstrogen can increase GAD activity in the posterior hypothalamus and ME (26, 27), but it is suggested that this is an indirect effect exerted via raised prolactin levels (25,36,38). Others have shown that OB treatment reduced GAD activity in the VMN, ARC and anterior hypothalamus, but not in the POA (24), however two further papers found no change in any of the hypothalamic areas investigated (9,23). Our own results support the latter findings in that we also found no change in GAD activity in the POA, VMN, ARC/ME or ZI.…”
Section: Ospmentioning
confidence: 99%
“…GABA-containing neurons possess steroid receptors (4,5 ) and it has becn suggested that sri:roids might exert some of their CNS effects via GABAergic s! stems (6)(7)(8)(9). These effects include the control of luteinizing hormone (LH) and prolactin release and sexual behaviour.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports show an effect of E, on the density of GABA receptors in the hypothalamus (40,41), therefore we theorized that oestrogenization may induce a regulation of GABA, receptors in the SCA. To study the in vivo effects of E, on GABA, and GABA, receptors we developed an in vitro quantitative autoradiographic method.…”
Section: Discussionmentioning
confidence: 91%